Understanding the value of digital marketing tools for SMEs - Morais, Elisabete Paulo (2020)
Digital marketing is gaining predominance in marketing strategies across the globe. Digitization is becoming more and more present in business, not just changes in consumer behavior, but the adoption of new technologies, tools, and applications is highly disruptive, with immediate impact on the business of all companies. The common link between digital marketing definitions is the use of tools, namely online tools. One of the biggest changes in human interaction is the recent proliferation of online social networks. Rapid growth of web-based platforms that facilitate online social behavior has significantly modified the nature of human activities, habitats, and interactions. Real-world social relationships have been migrated to the virtual world, resulting in online communities that bring people together from across the globe. This study aims to identify and describe the various digital marketing tools and which of these can be used to increase the SMEs competitiveness.